2019
DOI: 10.1111/boc.201900038
|View full text |Cite
|
Sign up to set email alerts
|

hVFL3/CCDC61 is a component of mother centriole subdistal appendages required for centrosome cohesion and positioning

Abstract: Background. The centrosome regulates cell spatial organisation by controlling the architecture of the microtubule (MT) cytoskeleton. Conversely, the position of the centrosome within the cell depends on cytoskeletal networks it helps organizing. In mammalian cells, centrosome positioning involves a population of MT stably anchored at centrioles, the core components of the centrosome. An MT-anchoring complex containing the proteins ninein and Cep170 is enriched at subdistal appendages (SAP) that decorate the ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…CCDC61/VFL3 might interact with a centrosomal and basal body-specific protein that is yet to be identified, and scaffold the protein with microtubules to construct regularly aligned basal body-associated structures. Two groups recently proposed that CCDC61 interacts with CEP170 and might play a role in the subdistal appendage function of centrioles (B€ arenz et al, 2018;Pizon et al, 2020). While our manuscript was under review, Pizon and colleagues also reported CCDC61 association with microtubules (Pizon et al, 2020), in agreement with our data.…”
Section: Ll Articlesupporting
confidence: 91%
See 2 more Smart Citations
“…CCDC61/VFL3 might interact with a centrosomal and basal body-specific protein that is yet to be identified, and scaffold the protein with microtubules to construct regularly aligned basal body-associated structures. Two groups recently proposed that CCDC61 interacts with CEP170 and might play a role in the subdistal appendage function of centrioles (B€ arenz et al, 2018;Pizon et al, 2020). While our manuscript was under review, Pizon and colleagues also reported CCDC61 association with microtubules (Pizon et al, 2020), in agreement with our data.…”
Section: Ll Articlesupporting
confidence: 91%
“…SAS6 assembly, for instance, is probably aided by its interaction with CEP135 and STIL (Dzhindzhev et al, 2014;Lin et al, 2013;Ohta et al, 2014), whereas for the XRCC4/XLF complex this function is exerted by its associations with DNA ligase IV, Ku70/80 and DNA (Ochi et al, 2014). Putative CCDC61 binding proteins, such as CEP170 (B€ arenz et al, 2018;Pizon et al, 2020) might play an equivalent role in CCDC61. Thus, the overarching principles of higher-order oligomerization and stabilization by other proteins appears to be conserved among the XRCC4 superfamily members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subdistal appendages, which are formed just below DAs, are usually robust electron densities that are highly variable in shape and in number ( Figure 1 C) [ 35 , 36 ]. On their periphery, SDAs are associated with MTs, which regulate MT centrosome positioning [ 37 , 38 , 39 , 40 , 41 ] and cohesion [ 42 ].…”
Section: The Organization Of Mature Centrioles and Centrosomesmentioning
confidence: 99%
“…The number and shape of SDAs is highly variable [ 35 , 36 ] even between the cells of the same cell type. The ends of SDAs are associated with MTs [ 39 , 40 ], which mediate centrosome positioning, directional cell migration, and centrosome cohesion [ 37 , 204 , 205 ]. DAs are positioned distally to SDAs [ 19 , 20 , 21 , 36 , 79 ] and look like nine finger-like protrusions, slightly curved toward the centriole distal end [ 19 ] ( Figure 1 A).…”
Section: Morphological and Biochemical Changes Of Centrioles Durinmentioning
confidence: 99%